Physical characterization and in vivo pharmacokinetic study of self-assembling amphotericin B-loaded lecithin-based mixed polymeric micelles - Chen YC (Dove Medical Press, 2015)
Ying-Chen Chen,* Chia-Yu Su,* Hua-Jun Jhan, Hsiu-O Ho, Ming-Thau Sheu School of Pharmacy, College of Pharmacy, Taipei Medical University, Taipei, Taiwan *These authors contributed equally to this work Abstract: To alleviate the inherent problems of amphotericin B (AmB), such as poor water solubility and nephrotoxicity, a novel self-assembling mixed polymeric micelle delivery system based on lecithin and combined with amphiphilic polymers, Pluronic®, Kolliphor®, d-alpha tocopheryl polyethylene glycol succinate, and 1,2-distearoyl-sn-glycero-3-phosphoethanolamine-N-methoxy(poly(ethylene glycol)-2000 (DSPE-PEG2K) was developed. An optimal formulation (Ambicelles) composed of AmB:lecithin:DSPE-PEG2K in a 1:1:10 weight ratio was obtained. The particle size, polydispersion index, drug encapsulation efficiency, and drug loading were 187.20±10.55 nm, 0.51±0.017, 90.14%, and 7.51%, respectively, and the solubility was increased from 0.001 to 5 mg/mL. Compared with that of Fungizone®, the bioavailability of Ambicelles administered intravenously and orally increased 2.18- and 1.50-fold, respectively. Regarding the in vitro cytotoxicity, Ambicelles had a higher cell viability than free AmB solution or Fungizone® did. With pretreatment of 50 µg/mL ethanolic extract of Taiwanofungus camphoratus followed by AmB to HT29 colon cancer cells, the 50% inhibitory concentration of AmB solution was 12 µg/mL, whereas that of Ambicelles was 1 µg/mL, indicating that Ambicelles exerted a greater synergistic anticancer effect. Keywords: amphotericin B, micelle, amphiphilic polymer, lecithin, DSPE-PEG